EXAMPLE OF QUALITY ASSURANCE OF TECHNOLOGY SUBJECT TEACHING AT HIGHER EDUCATION INSTITUTIONS - HASKOVA, Alena; Peter, KUNA; Eva, MALA (Trends in education, 2015)
In their paper, the authors briefly describe the aims and content of an international project focused on modernization of tertiary education in the target countries (Armenia, Georgia, Ukraine). The quality of teaching technical subjects is assured by providing practically oriented syllabi and modules in the embedded system environment, and by subsequent creation of remote laboratories in the target institutions.
Keywords: quality assurance; technology subject teaching; tertiary education; international projects.